Legionella pneumophila - Gonçalves, Inês G. (2021)
Legionella pneumophila is an intracellular pathogen, ubiquitous in the environment and considered opportunistic. It is the leading cause of legionellosis, which can be present in its nonpneumonic form (Pontiac fever) and acute pneumonic form (Legionnaires` disease – LD). In the soil and aquatic systems, L. pneumophila can invade and survive intracellularly in various protozoans. The ability to proliferate within biofilms provides additional protection from environmental stresses, such as disinfection. Human infection by L. pneumophila occurs after the inhalation or aspiration of aerosols containing the pathogen. Upon infection, alveolar macrophages can be invaded and used by L. pneumophila for replication, resembling the infection of protozoan hosts in the environment. The ability of L. pneumophila to overcome the killing mechanisms of phagocytes depends on the Dot/Icm type IV secretion system – a specialized protein translocation system vital for the intracellular survival of the pathogen and for establishing a replicative niche known as the Legionella-containing vacuole. Following host cell lysis, the released bacteria infect other host cells, beginning a new cycle of infection.